Pro Perl Parsing - Frenz, Christopher M.; SpringerLink (Online service) (Berkeley, CA : Apress : Imprint: Apress, 2005)
Perl, one of the world's most diffuse programming languages, was born out of the need to resolve the creator's dissatisfaction with what were at the time standard data-parsing solutions. Indeed, since the 1.0 release in 1987, Perl has been heralded for its powerful parsing capabilities features that are further enhanced through the thousands of Perl extensions made available through CPAN (the Comprehensive Perl Archive Network). Pro Perl Parsing begins with several chapters devoted to key parsing principles, discussing topics pertinent to regular expressions, parsing grammars, and parsing techniques. This material sets the stage for later chapters, which introduce numerous and powerful CPAN parsing modules, and provide an ample supply of example applications.
Parsing and Regular Expression Basics -- Grammars -- Parsing Basics -- Using Parse::Yapp -- Performing Recursive-Descent Parsing with Parse::RecDescent -- Accessing Web Data with HTML::TreeBuilder -- Parsing XML Documents with XML::LibXML and XML::SAX -- Introducing Miscellaneous Parsing Modules -- Finding Solutions to Miscellaneous Parsing Problems -- Performing Text and Data Mining.
Keywords: Computer programming; Software engineering; Web Development; Software Engineering/Programming and Operating Systems